2016
DOI: 10.1088/1367-2630/18/12/125001
|View full text |Cite
|
Sign up to set email alerts
|

Differential kinetic dynamics and heating of ions in the turbulent solar wind

Abstract: The solar wind plasma is a fully ionized and turbulent gas ejected by the outer layers of the solar corona at very high speed, mainly composed by protons and electrons, with a small percentage of helium nuclei and a significantly lower abundance of heavier ions. Since particle collisions are practically negligible, the solar wind is typically not in a state of thermodynamic equilibrium. Such a complex system must be described through self-consistent and fully nonlinear models, taking into account its multi-spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
89
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(98 citation statements)
references
References 75 publications
8
89
0
1
Order By: Relevance
“…The electric and magnetic spectra obtained in the two runs perfectly match, and reveal the typical features observed in solar-wind plasma. Indeed, similarly to previous numerical experiments Valentini et al 2016;Pezzi et al 2018a), an inertial-like range is observed, where the magnetic PSD recalls the Kolmogorov prediction (orange dashed-line) (Kolmogorov 1941), although a proper power-law scaling is not observed due to the limited size of the simulation domain. Around kd p ∼ 1, the usual spectral steepening is recovered (Leamon et al 1998).…”
Section: Evolution Of Turbulence At Proton Scalessupporting
confidence: 86%
“…The electric and magnetic spectra obtained in the two runs perfectly match, and reveal the typical features observed in solar-wind plasma. Indeed, similarly to previous numerical experiments Valentini et al 2016;Pezzi et al 2018a), an inertial-like range is observed, where the magnetic PSD recalls the Kolmogorov prediction (orange dashed-line) (Kolmogorov 1941), although a proper power-law scaling is not observed due to the limited size of the simulation domain. Around kd p ∼ 1, the usual spectral steepening is recovered (Leamon et al 1998).…”
Section: Evolution Of Turbulence At Proton Scalessupporting
confidence: 86%
“…Multi-spacecraft and high resolution measurements in the solar wind and in the terrestrial magnetosphere [12,13] have provided evidence of such interconnection [14]. The increasing performance of numerical simulations has also allowed processes on several scales to be examined, and therefore to highlight their relationship [15][16][17][18][19][20][21][22][23][24]. Theoretical efforts are also being carried out in order to highlight the specific processes governing the energy exchange between ranges associated to different regimes [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Matthaeus & Lamkin 1986;Biskamp 2008;Servidio et al 2010Servidio et al , 2011Lazarian et al 2012;Karimabadi et al 2013a;Servidio et al 2015;Franci et al 2016;. In this context, currents and coherent structures are typically related to simultaneous enhancement of vorticity, kinetic activity, turbulent transfer and dissipation (e.g., Servidio et al 2012Servidio et al , 2014Karimabadi et al 2013b;Valentini et al 2014Valentini et al , 2016Wan et al 2015;Franci et al 2016;Parashar & Matthaeus 2016;Yang et al 2017;Grošelj et al 2017;Camporeale et al 2018;Sorriso-Valvo et al 2018). Furthermore, reconnection/structures have been recently proved to enhance/trigger the kinetic turbulent cascades in real space Franci et al 2017;Camporeale et al 2018) and also to be related to simultaneous velocity space cascades (Servidio et al 2017;Cerri et al 2018;Pezzi et al 2018).…”
Section: A Broader View: Relevance To Other Instabilities and Turbulementioning
confidence: 99%